Legal Politics Electronic Land Certificate in Indonesia - Sukadi, Imam; Harry, Musleh; Setyobudi, Teguh; Sinal, Mohamad; As-Suvi, Ahmad Qiram (Universitas Semarang, 2024)
In accordance with National Land Agency Regulation No. 1 of 2021, this study investigates the adoption of electronic land certificates. The need to enhance land services in Indonesia, especially in the fight against the land mafia and the settlement of intricate agrarian disputes, is what makes this research so urgent. Creating an electronic certificate system is essential to updating public services in light of the rise in fraud and land ownership disputes. Significant obstacles stand in the way of digital transformation in land management, nevertheless, such as the requirement for a strong legal framework and prepared infrastructure. The novel aspect of the study is its evaluation of infrastructure preparedness for electronic certificates, a topic that has received little attention in earlier studies. The responsive law theory of Philippe Nonet and Philip Selznick is used in this analysis to emphasize how crucial adaptable legal frameworks are for addressing societal shifts. The results indicate that increasing digital infrastructure and raising public understanding of land technology are essential to the success of electronic land certificates. This invention has the potential to improve confidence in the National Land Agency and expedite the settlement of land disputes. According to Indonesian law, both paper and electronic documents are legitimate; nevertheless, for long-term use, rules pertaining to data security, technology, and public education need to be strengthened. The digital revolution of land administration requires cross-sector cooperation.